Studi Komparasi Hari Raya Galungan di Bali dan Wijaya Dasami India - Etika, Tiwi - (Fakultas Dharma Duta, 2022)
Galungan is a Balinese holiday, celebrating the victory of dharma (virtue) over adharma (evil). It is similar to Wijaya Dasami (Wijaya Dashami) and Durga Puja Nawaratri in India, celebrated by Hindus in other parts of the world. The word Dussehra is a variant of Dashahara which is a compound Sanskrit word meaning